A Comparative Study of Adsorption of Methylene Blue Dye onto Untreated Platanus orientalis (chinar tree) Leaves Powder and its Biochar - Equilibrium, Kinetic and Thermodynamic Study - Fairooz Ahmad Khan; Mushtaq Ahmad Bhat Mushtaq; Pathan Mohd Arif Arif; Mazahar Farooqui Mazahar (Orbital: The Electronic Journal of Chemistry, 2023)
In the present investigation the adsorption behavior of methylene blue (MB) dye from aqueous solution onto untreated chinar leaves powder (CLP) and chinar leaves biochar (CLB) has been studied. To find out optimum conditions, adsorption process was carried out by varying different parameters such as contact time, adsorbent dose, concentration, temperature, salts, and pH. The equilibrium adsorption data were subjected to different popular isotherms (Langmuir, Freundlich, and Temkin) and kinetic models (pseudo-first order, pseudo-second order and intra-particle diffusion model). The thermodynamic study was also done on the adsorption process. The maximum monolayer adsorption capacities for MB dye onto given adsorbents are 1.53 mg/g (CLP) and 1.02 mg/g (CLB). Also the values of RL and n suggest favourable adsorption process of MB dye onto CLP and CLB adsorbents. The pseudo-second order kinetic model is best obeyed by both the mentioned adsorbents for MB dye adsorption with R2 value equal to 1. Thermodynamic study reveals that the adsorption process of MB dye is spontaneous, endothermic (CLB) and exothermic (CLP). At an equilibrium time of 20 min the uptake efficiency (> 99%) was recorded for both the low cost adsorbents (CLP and CLB) thus proved them fast and effective adsorbents for the removal of MB dye.